2021
DOI: 10.1111/apt.16317
|View full text |Cite
|
Sign up to set email alerts
|

Comparative benefit and cost‐effectiveness of mailed‐out faecal immunochemical tests vs collection at the general practitioner

Abstract: SummaryBackgroundParticipation in the colorectal cancer screening programme in France has been well below the 45% considered acceptable by European guidelines, potentially attributable to the need to collect the faecal immunochemical test (FIT) at the general practitioner.AimTo estimate the potential benefits and costs of including the FIT in the invitation letter.MethodsA well‐established microsimulation model was used to simulate the French population 35 years and older in 2018. We estimated quality‐adjusted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Nevertheless, there are other mechanisms as well that have been shown to further increase participation including advance notification letters, and sending reminder letters to nonresponders (Rat et al , 2018). Recent analyses comparing different invitation strategies in Hungary and France (Csanádi et al , 2021; Peterse et al , 2021), showed that even at minimal increases in participation, all investigated strategies to enhance participation were cost-effective. With observed adherence only slightly above 30% in the pilot, these studies provide a strong argument for policymakers to consider improving the invitation strategies in Slovakia and support the implementation of these changes with further cost-effectiveness analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there are other mechanisms as well that have been shown to further increase participation including advance notification letters, and sending reminder letters to nonresponders (Rat et al , 2018). Recent analyses comparing different invitation strategies in Hungary and France (Csanádi et al , 2021; Peterse et al , 2021), showed that even at minimal increases in participation, all investigated strategies to enhance participation were cost-effective. With observed adherence only slightly above 30% in the pilot, these studies provide a strong argument for policymakers to consider improving the invitation strategies in Slovakia and support the implementation of these changes with further cost-effectiveness analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The Slovenian CRC screening program invites individuals to perform two fecal samples of the OC-sensor (Eiken, Japan) FIT, which is analyzed at a cutoff 20 μg Hb/g feces. Data on screening complications rates and utilities were based on literature (Warren et al , 2009; Peterse et al , 2021).…”
Section: Methodsmentioning
confidence: 99%